Psychosocial and structural barriers to dual careers among Korean student-athletes: a multilayered ecological perspective - Ha, Seong Jun (Frontiers in Psychology, 2025)
IntroductionThis qualitative study investigates psychosocial and structural barriers to dual careers faced by Korean student-athletes. In South Korea, coexistence of the elite-centered sports culture and exam-driven education system poses significant challenges for student-athletes seeking to balance their academic and athletic goals.MethodsThis study is grounded in Bronfenbrenner’s ecological systems theory and explores interactions across five ecological levels: microsystem (parents and coaches), mesosystem (school-sport relationships), exosystem (institutional structures), macrosystem (sociocultural norms), and chronosystem (policy timing). Data were collected through in-depth, semi-structured interviews with 20 participants, including student-athletes, coaches, parents, and teachers. Thematic analysis was conducted using a multilevel coding process.ResultsFive core themes emerged: (1) narrow and fragmented career awareness influenced by close stakeholders, (2) passive compliance with sports-centered expectations in school and family systems, (3) structural constraints within athlete development and admissions systems, (4) sociocultural pressure stemming from South Korea’s competitive university entrance landscape, and (5) misalignment between dual-career policy intentions and field-level implementation timing.DiscussionThese findings illustrate how systemic interactions across ecological levels restrict student-athletes’ abilities to pursue dual careers in South Korea. To address these barriers, this study recommends integrated policy strategies that promote institutional flexibility, inter-stakeholder collaboration, and cultural acceptance of diverse career pathways. This research provides practical insights for improving dual-career systems in centralized sports structures, drawing on global models such as the EU Guidelines on Dual Careers of Athletes.